Surgical anatomy and clinical variation of the left colonic artery in laparoscopic anterior rectal resection - Li, Jiajun; Zhao, Xiaofang; Yi, Bo; Fu, Chuanchuan; Xu, Peipei; Chen, Chao; Zhao, Bin; Zheng, Yangchun (Frontiers in Surgery, 2024)
Objectives This study aims to investigate the surgical anatomy and clinical variation of the left colonic artery (LCA) during laparoscopic anterior rectal resection. Methods We conducted a retrospective analysis of 87 patients diagnosed with colorectal cancer who underwent laparoscopic anterior rectal resection with preserved LCA at the Department of Gastroenterology, Sichuan Cancer Hospital, between March 2018 and April 2022, aiming to observe the emanation location, anatomical typing, and travel trajectory of the LCA, as well as its relationship with the inferior mesenteric vein (IMV). Results In all observed cases, we observed that the LCA emanated from the left side of the inferior mesenteric artery (IMA), and the average distance from the root of the IMA to the emanation of the LCA was approximately 3.5 ± 1.1 cm. Specifically, 35 of these cases had the LCA branching from the IMA alone (Type I, 40.2%),16 cases had the LCA cotruncating with the sigmoid artery (SA) (Type II, 18.4%), 30 cases had the LCA cotruncating with the superior rectal artery (SRA) and SA (Type III, 34.5%), and six cases had the LCA cotruncating with four or more branches of the SRA and SA (Type IV, 6.9%). No LCA agenesis cases were found in this group. In addition, we also observed the occurrence of LCA alignment. Specifically, there were 25 cases where the LCA crossed the IMV in a diagonal upward direction (Type A, 28.7%), 36 cases where the LCA crossed the IMV in an upward arched manner (Type B, 41.4%), 18 cases where the LCA crossed the IMV in a vertical outward direction (Type C, 20.7%), and eight cases where the LCA crossed the IMV in a diagonal downward manner (Type D, 9.2%). Among them, two cases developed anastomotic fistula, one case had chyle leakage 1 week after surgery, and four cases experienced urinary retention; all of the patients successfully recovered and were discharged after receiving conservative treatment. Conclusion The anatomy and variation of the LCA can be clearly and accurately observed during laparoscopic surgery. Understanding the type and variation of the LCA helps to dissect the vessels in the IMA region during surgery, particularly in cases when the LCA is preserved, and reduce the incidence of vascular injury and its complications.